Evaluation of Entrepreneurship Education on Development Program of Product Sorghum - Noerhartati, Endang (International Journal of Engineering and Technology, 2018)
This study aims to evaluate and expand the educational entrepreneurship program based on sorghum products. Education entrepreneurship is a compulsory subject for students Agroindustrial Technology Department. Sorghum is one of the potential industrial materials as raw material of entrepreneurship activities. Data were taken through observation, questionnaire, and interview on sixth semester students. Observations focused on responses from practice, responses to commission business opportunities, and observed the output of beginner entrepreneurs practiced. Data were analyzed statistically, to improve the entrepreneurship education process and to develop the sorghum business in Indonesia. In the education process is accompanied by Center for Sorghum Entrepreneurship (CSE). The results achieved create new educated sorghum-based entrepreneurs, produce healthy entrepreneurship products, and mentoring processes by CSE should be implemented continuously in the development of entrepreneurship education programs and to develop a business of sorghum-based products, so can achieve its goal that is to support the food security and sovereignty program of the Government of Indonesia.Â Â